Relation between corporate governance attributes and financial performance in oil and gas industries - Ong, Tze San; Teh, Boon Heng; Ahmad, Nuranisma; Muhamad, Haslinah (Faculty of Business and Economics, University of Malaya, 2015)
This study explores the relationship between the structure of company board of directors (BOD) and financial performance looking at a sample of Malaysian oil and gas companies. In order to show a link exists between BODs and financial performance of a firm, the authors examined 28 Malaysian oil and gas companies listed on Bursa Malaysia, using annual data from 2007–2011 fiscal years. A multiple regression analysis examined the relationship between the characteristics of BODs and the firms performance relying on financial ratios namely, Return on Equity (ROE) and Return on Assets (ROA). Measures of corporate governance attributes employed are: composition of the board, CEO/Chairman duality, board size, independence of nomination committee and a risk management committee. The results revealed that an effective board size had a positive impact on financial performance for the Malaysian oil and gas industry but was the study was unable to establish if composition of the board and existence of risk management had a role. Interestingly, the findings indicate that independence of nomination committee and non-dual leadership structure are significantly and inversely related to financial performance. The outcome of the study implies that in pursuing the true spirit of corporate governance, having a board that is truly independent of management, with an appropriate number of directors is deemed vital for good financial performance.